FOREST TYPOLOGY STRUCTURE AND PRODUCTIVITY OF PEDUNCULATE OAK FOREST STANDS OF DIFFERENT ORIGIN IN THE SUMY REGION - Chygrynets, V. P.; Ihnatenko, V. A.; Tarnopilsky, P. B. (Forestry and Forest Melioration, 2018)
A forest typology analysis are made for oak forest stands of different origin at forest enterprises of Sumy Regional Department of Forestry and Hunting, located in the forest-steppe zone. According to the types of forest site conditions, the distribution of oakeries in area and their forest inventory indexes are analyzed and their growth and productivity are assessed. In edatopes of fresh fertile site type and fresh fairly fertile site type there are 93.7 % of area of oak forest stands. It is found that the wood volume of dense oak forest stands of Sumy region in edatope D2 is 5–28 % higher depending on the age and origin compared to the average one in Ukraine. The natural seminal and artificial seminal forest stands have the best growth by wood volume.